Perancangan aplikasi android tanaman hias dengan metode UX Interface untuk memacu daya agribisnis ibu rumah tangga (Studi kasus di kecamatan Palaran, Kalimantan Timur) - Rizka Indah Armianti; Banung Grahita (Institut Seni Indonesia Yogyakarta, 2023)
Ornamental plants are plants that have aesthetic value in terms of color, shape, and characteristics. Planting and maintaining ornamental plants has now become a hobby that housewives are interested in, especially in the Palaran sub-district, East Kalimantan. Housewives take advantage of their free time to do quality and business value things and generate side income, one of which is farming. The ornamental plant business is an agribusiness business. Agribusiness is a business activity of cultivating agricultural products both on a narrow and wide scale. However, it is difficult to find a contractor, demotivating housewives in the ornamental plant business. This raises the need for technology that can provide information, bring together sellers and contractors in a practical way, with minimal costs, able to communicate and transact at any time. From these problems, an Android-based Mobile E-Commerce application was designed using the UX Interface by JJ method. Garrett. The application that has been designed is then tested for usability using a measuring tool for effectiveness, efficiency, and user satisfaction. The usability value obtained is 88.69%. This proves that the application designed has helped users in caring for ornamental plants and has created a desire to do ornamental plant business because they get relevant price recommendations and information on what plants are currently hot so that the collection of ornamental plants which can be of commercial value.